Synergizing multi-criteria diagnosis for safeguarding cultural heritage and the restoration of vanished legacy: A historical exploration in science, technology, and archaeology - Sana Simou; Khadija Baba; Abderrahman Nounah (History of science and technology, 2023)
The urgent need to preserve cultural heritage is starkly evident in contemporary society, particularly poignant in Morocco where its rich cultural legacy faces unprecedented threats. The rapid forces of urbanization and relentless economic development have converged, resulting in the alarming devaluation and irreversible degradation of a substantial portion of this invaluable heritage. Within this disconcerting backdrop, certain remarkable vestiges have managed to endure the ravages of time. One such exemplar is the Marinid Madrasa, an architectural marvel from the 4th century, nestled within the Chellah archaeological site in Rabat, Morocco. Beyond its physical grandeur, the Madrasa plays a pivotal role as a conduit between the past and the future, facilitating the transmission of cultural heritage to generations yet unborn. This paper embarks on a multidisciplinary journey, employing advanced techniques such as terrestrial photogrammetry, numerical modeling, and specialized archaeological characterization, to undertake comprehensive diagnostic study processes. The convergence of these diverse methodologies lays a robust foundation for a holistic diagnostic study. This endeavor serves not only academic curiosity but becomes the cornerstone upon which strategies for compatible conservation and restoration interventions are erected. In the intricate interplay between historical preservation and the imperatives of progress, these methodologies form a bridge. This bridge links the architectural magnificence of the Madrasa with the imperatives of safeguarding it in a rapidly changing world. The ultimate aspiration of this multidisciplinary approach is twofold: to ensure the enduring protection of the Marinid Madrasa and other archaeological remnants against the erosive forces of time and urban development, and to forge a narrative that sensitively navigates the challenges posed by preserving cultural heritage in the face of modernity. In this endeavor, advanced technologies are interwoven with a profound recognition of the historical, social, and cultural significance of these sites, ultimately charting a course that not only conserves architectural brilliance but also honors the profound stories they encapsulate across the epochs.